Photophysical and anion sensing properties of a triphenylamine–dioxaborinine trimeric compound. Issue 3 (9th January 2023) - Tigreros, Alexis; Bedoya-Malagón, Camilo; Valencia, Alejandra; Núñez-Portela, Mayerlin; Portilla, Jaime
Abstract : The one-pot triphenylamine functionalization with multiple dioxaborinine groups gives the novel dye A2 with two-photon absorption and cyanide-sensing properties. The solvatofluorochromism of A2 was interpreted in terms of solvent dipolarity. Abstract : Herein, we report the synthesis and photophysical characterization of the novel tris(4-(2, 2-difluoro-6-methyl-2 H -1λ 3, 3, 2λ 4 -dioxaborinin-4-yl)phenyl)amine trimeric probe (A2 ) via the reaction between triphenylamine (1 ), acetic anhydride, and BF3 ·OEt2 implying the twelve new bond formation in a one-pot manner. This highly fluorescent compound in solution ( φ up to 0.91 at 572 nm) and solid state ( φ = 0.24 at 571 nm) showed a better solvatofluorochromism than its analog monomeric A1 due to symmetry-broken charge transfer, which is consistent with high solvent dipolarity (SdP) response in Catalán's multiparametric regression. Notably, A2 had a high sensibility and selectivity for CN − or F − in solution (LODCN − /F − = 0.18/0.70 μM), and CN − can be discriminated from F − by the reaction of A2 with 3.0 equiv. of CN − . In addition, A2 was impregnated on filter paper to prepare test strips that were applied to naked-eye qualitative sensing of CN − or F − . Finally, the octupolar system in A2 allows for better action of two-photon excitation cross-section values when compared with that of the dipolar structure in A1 . These findings provide further information for the design of new efficient two-photon absorption dyes.